World Bank Research Digest, Vol. 9(3) - World Bank (Washington, DC, 2015)
In this issue: The State as Employer of Last Resort in Postrevolution Tunisia; What Drives Weak Job Creation in Tunisia?; Macroinsurance for Microenterprises; Testing the Effectiveness of Job Matching in Jordan; Predicting Bank Insolvency in the Middle East and North Africa; Economic Inequality in the Arab Region; Open Skies over the Middle East.